Serum Beta2-Microglobulin Levels in Hepatitis B e Antigen-Negative Chronic Hepatitits B Patients under Long-Term Lamivudine Monotherapy: Relationship with Virological Breakthrough - Ioannis S Elefsiniotis; Nikolaos Scarmeas; Irene Glynou; Konstantinos D Pantazis; Helen Kada; Christos Mavrogiannis (Canadian Journal of Gastroenterology)
OBJECTIVES: To evaluate the predictive value of serum beta2-microglobulin (β2m) levels for virological breakthrough in hepatitis B e antigen-negative chronic hepatitis B patients under long term lamivudine monotherapy.